PENERAPAN TEKNOLOGI SMART MANUFACTURING DALAM MENJAGA KONTINUITAS PRODUKSI PADA PT AMERTA INDAH OTSUKA - Lis Setyowati; Nur Aini Anisa; Aurel Indi Febya Lukita; Galung Perwira Buana; Salsabilla Diva Rosalinda; Vandia Velda Alinsky; Selvia Noer Rahma (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
The transformation toward Industry 4.0 requires manufacturing companies to adopt technologies capable of ensuring operational stability and sustainability. This study aims to analyze the implementation of smart manufacturing technology at PT Amerta Indah Otsuka and its impact on the continuity of the isotonic drink production process. The research method employed is descriptive qualitative, with data collection techniques including direct observation at the production facility and literature studies related to automation systems. The research focuses on the integration of automated production machinery, the use of real-time quality monitoring sensors, and robotic packaging systems that minimize human intervention. The results indicate that the use of smart manufacturing technology enables the company to achieve high production efficiency, reduce the risk of human error, and ensure that product sterility standards are consistently maintained. Production continuity is supported by programmed machine maintenance systems and digitally integrated production line monitoring. This study concludes that investment in automation technology not only increases output capacity but also serves as a crucial strategy in maintaining the company's operational resilience amidst the dynamics of the FMCG industry.